Trends of the Electricity Market Establishment - Štilinis, Rimvydas (Ekonomika, 2006)
Since January 1, 2002, when the Law on Electricity came into force, the electricity market started functioning in Lithuania, whereby choosing the supplier of electricity is done based on the quality of service and pric. The essence of the electricity market is a customer’s right to choose an electricity supplier and price, and the goal being to create conditions for competition and to effectively manage the electricity sector. Although 74% of the market is opened in Lithuania from the legal point of view, in practice this privilege is used by those market players who were able to use it earlier according to the Law on Electricity which came into force in 2000. The Lithuanian electricity market is not very effective, because it is quite small, the market players differ significantly, and the competition is limited: the Herfindahl-Hirschman index for generation utilities is equal to 5562 regarding the installed capacity of the Lithuanian power plants. The implication is that nowadays the competition is not realistic in the closed Lithuanian electricity market, because electricity generation is not controlled and there is a risk that the competition will be limited if even electricity generation comes under control. Thus, as long as the common Baltic electricity market (CBEM), or the Baltic regional electricity market is not created, we will have a strongly controlled and regulated electricity market model although functioning according to the European Union (EU) Directives. Aanalysis of establishing the common Baltic electricity market was prepared using the SWOT as a strategic planning tool, and the main results are presented: its strengths, weaknesses, opportunities, and threats. Quoting the Lithuanian, Latvian and Estonian energy systems’ forecast data to 2012 for generation and demand and assuming that the common Baltic electricity market with numerous market players is functioning; the above mentioned market concentration was calculated and the results are presented: the Herfindahl-Hirschman index for generation utilities is equal to 891 in 2010. The main conclusion is that establishing the common Baltic electricity market is a sufficient step towards a competitive and effective electricity market functioning under the best market model standards.Nowadays, the first steps are being made and the next stages are planned concerning the common Baltic electricity market’s external competition from the eastern and western parts of the energy systems. This can be stimulated by the unique connections within the Baltic countries, allowing electricity supply without any restrictions, and by the capacity of interconnections, which is enough for securing free trading among the Baltic countries for a needed period. Another opportunity is integration to the West European electricity markets (the Baltic Ring connecting Scandinavian and Baltic electricity markets). In 2004, Baltic companies and two Scandinavian companies have established the “Nordic Energy Link” company which is responsible for the coordination of interconnection of the electricity systems via the Estlink sea cable; furthermore, some Swedish companies proposed involving Lietuvos Energija AB into the SwindLit project - connection of the Swedish and Lithuanian electricity systems. The implementation of the projects will enable integration of Lithuania and the other Baltic counties into the Nordic electricity market (Nord Pool) and herewith starting the first steps towards the integrated European Union (EU) internal electricity market.